Professoras iniciantes: relações entre a formação inicial e a prática do planejamento curricular - ROCHA, Érika D’Ávila de Sá (2019)
This research purpouse to analyze the relationships between initial training and curricular planning practice, by newly teachers adopting as main source their oral narratives. This work had as a starting point the following question: What are the relationships between initial training and the practice of curricular planning by new teachers? The main objectives of this research was: Investigate aspects of the initial formation of the beginning teachers that relate to the practice developed by them in the curricular planning; to verify the reception and the accompaniment of the school in the curricular planning, and more, to identify the curricular reference documents that the beginning teachers use in the accomplishment of the planning. We chose five female primary and elementary teachers from four municipal schools in Imperatriz, state of Maranhão participated in this study. We use theoretical and methodological contributions by Hurberman (2000), Cavaco (1999), Veenman (1984), Silva (2003), Tanuri (2000) and Vigotsky (2001) among others. For the production of the data, we used questionnaires to the coordinators and managers, a semistructured interview with the coordinator of the pedagogical advice of the Municipal Department of Education - SEMED, a field note for the moments of observation, and the main source of data: narrative interviews of the newly teachers, in an attempt to revisit their training paths and achieve the proposed objectives. Narrative interviews were analyzed from the Schütze proposal (2011) come in three axes: a) trajectories of the initial training of the beginning teachers; b) the beginning: the clash with reality; c) the curricular planning of the beginning teachers and the manifestations of support. The results denote that the beginning teachers have the sensation that the initial formation was not enough to assist them in their curricular planning practices. We also verified that the doubts and clarifications regarding the organization of the plans are attended by colleagues who are more experienced teachers, and not always by the management and coordination of the school. To select content and themes at the planning stage, most teachers use school textbooks or purchased collections and research on the internet. Through the narratives, we present in detail, excerpts from the formative trajectory of each teacher, their difficulties at the beginning of the profession and the construction of their teaching identity.